The role of multiple vessel doppler ultrasound in predicting neonatal outcome in pregnancy induced hypertension - Gadhavi, Vijay N.; Gadhavi, Mansi K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypertensive disorders are among the commonest medical disorders during pregnancy and continue to be a major cause of maternal and perinatal morbidity and mortality. Methods: In this study total 100 cases and their doppler findings were recorded, Cases of PIH between 20 - 36 weeks of gestation in 2 years with B.P ≥140/90 mm hg and protienuria ≥1+ in this prospective analytical study investigations and color doppler scanner for studying uterine, umbilical PI, RI and fetal middle cerebral arteries as the indicator to evaluate perinatal outcome. Results: Increase incidence of low birth weight (less than 2.5) observed in group of umbilical and uterine PI was (>1.5,>1 respectively)67% and 83%. Apgar score at 5 minutes <7 58%and 61%, NICU admission 46% and 45%, perinatal mortality 42%and 45% respectively. for group of umbilical artery and uterine artery RI (>0.7, >0.6respectively) newborn delivered with weight less than 2.5 kg 76% and 80%, Apgar score at 5 minutes <7 33% and 80%, NICU admission 46% and 50%, perinatal mortality 60%and 42% more than that of with group of low RI. High rate of incidence seen where MCA PI < 1.3,90% newborns less than 2.5 kg birth weight,70% poor Apgar score at 5 minutes. abnormal ductus venosus group shows birth weight <2.5 kg 83%, Apgar at 5 minutes < 7 were 81%, NICU admission were 39%and perinatal mortalities 78% higher than normal ductus venosus group. Conclusions: The sensitivity of the Doppler significantly increased by studying multiple vessels (91.6%) of in the fetoplacental circulation. It would predict early compromise of blood supply to the fetus at the stage when the fetus is still not compromised and if timely measures are taken it helps in improvement of perinatal out-come.